Efficacy of Emotionally Focused Couple Therapy on Marital Adjustment of Spouses in Churches in Benin City, Nigeria - Wellington, Jesuorobo Omosefe; MaryAngela, Otuonye Ijeoma (Universitas Mercu Buana Yogyakarta, 2023)
The study investigated the efficacy of Emotionally Focused Couple Therapy in managing marital adjustment among Christian Baptist spouses in Benin City Edo State. Two research questions were raised to guide this study and two corresponding hypotheses were formulated and tested at 0.05 level of significance. The study adopted the true experimental research design, using a non-equivalent pre-test and post-test control group. The target population of the study consisted of all the 3290 Baptist spouses in Benin City. A sample size of 61 spouses participated in the study. A multistage sampling method was used in selecting the samples for this study. A dyadic Adjustment Scale was administered to the spouses. The data collected were analyzed using paired t-tests and independent sample statistics. The findings of the study revealed that EFCT was effective in managing the marital adjustment of spouses. The study also found that there was a significant difference in the marital adjustment of spouses exposed to EFCT and control at the post-test. Based on the findings, it was recommended that counselling psychologists should take advantage of the proven efficacy of Emotionally Focused Couple Therapy in helping spouses to improve the quality of their marital relationship.